1996
DOI: 10.1021/jp961297j
|View full text |Cite
|
Sign up to set email alerts
|

The Electron Pair

Abstract: Eighty years have elapsed since Lewis introduced the concept of an electron pair into chemistry where it has continued to play a dominant rôle to this day. The pairing of electrons is a consequence of the Pauli exclusion principle and is the result of the localization of one electron of each spin to a given region of space. It is the purpose of this paper to demonstrate that all manifestations of the spatial localization of an electron of a given spin are a result of corresponding localizations of its Fermi ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
230
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(247 citation statements)
references
References 57 publications
13
230
0
Order By: Relevance
“…6 It is has been shown that the Laplacian of the charge density and ELF perform partitions of the molecular space which are consistent with the Lewis description and with the VSEPR model. 39,[42][43][44][45][46] The topology of the charge density Laplacina has been studied 38 51 and D h (r) is the kinetic energy of the homogeneous electron gas of density F(r). The excess local kinetic energy defined by eq 2 is the difference between the definite positive kinetic energy density T s (r) ) 1 / 2 ∇∇′F(r,r′)| r′)r and the von Weizsäcker 52 functional T W (r) ) 1 / 8 ∇F(r,r′)| 2 /F(r,r), where F(r,r′) is the first-order density matrix.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…6 It is has been shown that the Laplacian of the charge density and ELF perform partitions of the molecular space which are consistent with the Lewis description and with the VSEPR model. 39,[42][43][44][45][46] The topology of the charge density Laplacina has been studied 38 51 and D h (r) is the kinetic energy of the homogeneous electron gas of density F(r). The excess local kinetic energy defined by eq 2 is the difference between the definite positive kinetic energy density T s (r) ) 1 / 2 ∇∇′F(r,r′)| r′)r and the von Weizsäcker 52 functional T W (r) ) 1 / 8 ∇F(r,r′)| 2 /F(r,r), where F(r,r′) is the first-order density matrix.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…The function f ELF is a continuous scalar field and can therefore be subjected to a topological analysis similar to that used for the electron density by Bader [16]. This approach has been extensively used to highlight features of the ELF related to the chemical bonding in systems at zero field.…”
Section: Topological Analysismentioning
confidence: 99%
“…The ELF has been widely applied to understand bonding in atoms [3], molecules [4][5][6][7][8][9], clusters [10][11][12][13], and solid-state structures [14,15]. A topological analysis of ELF in the spirit of Bader's atoms-in-molecules approach [16] yields further information on bonding in a given system [2,[17][18][19][20], although some caution should be exercised in interpretations based on this analysis [21].…”
Section: Introductionmentioning
confidence: 99%
“…The delocalization index (DI) is a measure of number of electrons that are shared or exchanged between two atomic basins from integration of the Fermi hole density through a pair density matrix. 47,[50][51][52][53][54] The B3LYP functional has an exchange-correlation contribution from Slater determinant and the exchange-correlation potential-energy density. 41 Then, the density matrices of the density functional theory (DFT) yield similar results to post-Hartree-Fock theories like MP2 (see Supplementary Information).…”
Section: Rationalementioning
confidence: 99%
“…It is also important to remark that the sum of all localization indexes and half DI´s (because each atomic pair has the same DI) yields the total population of the molecular system. 47,[50][51][52][53][54] The delocalization index of very weak CC interactions lies between 10 -2 and 10 -3 order of magnitude. The DI value of 10 -1 order of magnitude for CC bonds is characteristic of moderate CC interactions (See Supplementary Information).…”
Section: Rationalementioning
confidence: 99%